Measurement of Capsaicinoids in Chiltepin Hot Pepper: A Comparison Study between Spectrophotometric Method and High Performance Liquid Chromatography Analysis. (20th January 2015) - González-Zamora, Alberto; Sierra-Campos, Erick; Pérez-Morales, Rebeca; Vázquez-Vázquez, Cirilo; Gallegos-Robles, Miguel A.; López-Martínez, José D.; García-Hernández, José L.
Abstract : Direct spectrophotometric determination of capsaicinoids content in Chiltepin pepper was investigated as a possible alternative to HPLC analysis. Capsaicinoids were extracted from Chiltepin in red ripe and green fruit with acetonitrile and evaluated quantitatively using the HPLC method with capsaicin and dihydrocapsaicin standards. Three samples of different treatment were analyzed for their capsaicinoids content successfully by these methods. HPLC-DAD revealed that capsaicin, dihydrocapsaicin, and nordihydrocapsaicin comprised up to 98% of total capsaicinoids detected. The absorbance of the diluted samples was read on a spectrophotometer at 215–300 nm and monitored at 280 nm. We report herein the comparison between traditional UV assays and HPLC-DAD methods for the determination of the molar absorptivity coefficient of capsaicin (ε 280 = 3, 410 andε 280 = 3, 720  M −1  cm −1 ) and dihydrocapsaicin (ε 280 = 4, 175 andε 280 = 4, 350  M −1  cm −1 ), respectively. Statistical comparisons were performed using the regression analyses (ordinary linear regression and Deming regression) and Bland-Altman analysis. Comparative data for pungency was determined spectrophotometrically and by HPLC on samples ranging from 29.55 to 129 mg/g with a correlation of 0.91. These results indicate that the two methods significantly agree. The described spectrophotometric method can be routinely used for total capsaicinoids analysis and quality control in agricultural and pharmaceutical analysis.